Antibiotic allergy: outcome of oral challenge. (29th September 2015) - Ho, S; Jay, N
Abstract : Introduction: Many children who are thought to have antibiotic allergy may in fact not be so. Children who have this unnecessary label of drug allergy are subjected to lifelong avoidance and possibly being prescribed less effective and more costly treatment. Investigations in these children are challenging and may include skin prick tests, drug radioallergosorbent test (RAST) level and oral challenge. Aim: The authors want to look at the outcome of our oral antibiotic challenge, the adverse effect and how it relates to clinical history, skin prick test and RAST levels. Methods: The authors retrospectively collected data of children (0–16 years old) who underwent drug challenges in our day care unit and for the subsequent 5 days at home with instructions to inform the team with any symptoms suggestive of allergy. The data are from January 2007 to July 2009. Data were collected from review of case notes and were systematically analysed. Results: The authors had 71 cases over that time period. Most of them have been referred by the general practitioner (39, 55%). Seven cases (9.8%) did not have any previous positive history of antibiotic allergy but were referred due to concerns over strong family history. The most common antibiotic being challenged is amoxicillin followed by penicillin. All cases had either or both skin prick test or RAST level being negative except for one case where none of these tests were done but the antibiotic challenge was successful. The authors had only one (1.4%) failed oral antibiotic challenge. This child had a negative skin prick test and RAST level. It was manifested as a mild rash on legs after 2.5 ml of antibiotics in day care unit. The child was given antihistamine and symptoms resolved. This child has not had any positive reactions in the past but was tested due to strong family history of antibiotic allergy. Conclusion: Over the 2 ½ years, the authors had only one failed oral antibiotic challenge (1.4%), which re-iterates the fact that true antibiotic allergy is not common. From our data, this shows that a positive clinical history correlates poorly to true antibiotic allergy.